ANALISIS NILAI RETURUN ON ASSET RETURN ON EQUITY PERUSAHAAN BATUBARA DI BURSA EFEK INDONESIA - Try Bunga Manurung; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Return on assets is a company's financial ratios related to profitability measuring the company's ability to generate profits or profits at a certain level of income, assets and share capital. Return on equity is part of the profitability ratio for this ratio shows the success of management in maximizing returns to investors. The data used are financial statement data published on the Indonesia Stock Exchange from 2018 to 2020, from which five companies selected as sample in this research. The results show that, based on the average return on assets, the five sampled companies are classified into very healthy criteria, with the ROA values of PT. Adaro Energy Tbk (5%), PT. Baramulti Suksessarana Tbk (17%), PT. Bayan Resources Tbk (27%), PT. Samindo Resources Tbk (17%), and PT. Harun Energy Tbk (8%). Moreover, based on the average return on equity, PT. Adaro Energy Tbk and PT. Harun Energy Tbk are classified into quite healthy criteria, with the percentages of 8% and 9%, respectively. Meanwhile, PT. Baramulti Suksessarana Tbk, PT. Bayan Resources, and PT. Samindo Resources Tbk are categorized into very healthy criteria, with the percentages of 27%, 49%, and 22%, respectively.